Woodworking FAQ : the workshop companion : build your skills and know-how for making great projects - Carlsen, Spike, 1952- (Storey Pub., 2012)
Answers commonly asked woodworking questions for beginning and experienced crafters alike, addressing issues pertaining to wood, tools, fasteners, joints, building furniture and cabinets, sanding and finishing, and performing repairs.